Membentuk Karakter Siswa Melalui Pembelajaran Seni Rupa di SMP Islam Pacet - Firdaus, Angga Eriksa; Purwanda, Eka (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to examine the role of fine arts learning in character formation of students at Pacet Islamic Middle School using a neuroaesthetic approach. Fine art is not only seen as a medium for visual expression, but also as a means of cognitive and emotional development that contributes to the formation of positive characters, such as creativity, discipline, cooperation and responsibility. A neuroaesthetic approach is used to understand how students' brains respond to aesthetic stimuli in the art learning process and how these experiences influence the development of moral and ethical values. This research uses qualitative methods with data collection techniques in the form of observation, interviews and documentation. The research subjects involved class VIII students at Pacet Islamic Middle School. The research results show that fine arts learning is able to stimulate students' character development through various creative and aesthetic activities. Visual stimulation provided through fine art media influences brain functions related to emotion and cognition, which in turn facilitates the formation of better character. The conclusion of this research is that fine arts as part of education not only improves students' aesthetic abilities, but also makes a significant contribution to the formation of their character. Therefore, fine arts learning should be integrated more deeply into the educational curriculum to optimize student potential, both in terms of academics and character formation.